Application of Sepic Converters as Solar Panel Output Voltage Stabilizers to Increase Access to Renewable Energy in Rural Communities - Yazid Ihsanudin; Edy Prasetyo Hidayat; Anggara Trisna Nugraha (Politeknik Perkapalan Negeri Surabaya, 2024)
The increasing demand for electricity in modern society necessitates innovative solutions, particularly in rural areas with limited access to reliable energy sources. Solar power, utilizing photovoltaic (PV) technology, has emerged as a sustainable energy solution. However, the challenge lies in ensuring that the voltage output from solar panels aligns with the requirements of energy storage systems, such as batteries. This research explores the application of a SEPIC converter as a voltage stabilizer for a 30W solar panel, aimed at improving the reliability of renewable energy in rural communities. In this study, two 30Wp polycrystalline solar panels are configured in series to generate a variable output voltage ranging from 5V to 17V. To charge a 24V battery, a SEPIC converter is employed to adjust the voltage, ensuring that it meets the battery's requirements. The converter's duty cycle, controlled by an Arduino Uno, regulates the voltage output. Testing reveals that the SEPIC converter successfully stabilizes the output voltage, with an average of 24.26V, meeting the desired set point. This solution provides a reliable and sustainable energy source for rural communities, promoting the use of renewable energy while addressing the voltage stability issue. The study highlights the practical application of the SEPIC converter in enhancing energy access and supporting community empowerment through renewable technology.